2009
DOI: 10.3858/emm.2009.41.7.056
|View full text |Cite
|
Sign up to set email alerts
|

Sodium tanshinone IIA sulfonate attenuates angiotensin II-induced collagen type I expression in cardiac fibroblasts in vitro

Abstract: Cardiac fibrosis occurs after pathological stimuli to the cardiovascular system. One of the most important factors that contribute to cardiac fibrosis is angiotensin II (Ang II). Accumulating studies have suggested that reactive oxygen species (ROS) plays an important role in cardiac fibrosis and sodium tanshinone IIA sulfonate (STS) possesses antioxidant action. We therefore examined whether STS depresses Ang II-induced collagen type I expression in cardiac fibroblasts. In this study, Ang II significantly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…The herbal compounds such as sodium tanshinone IIA [34] and resveratrol [29] exhibit beneficial effects on injured heart. Previous studies suggested that Gen protects against myocardial ischemia/reperfusion injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…The herbal compounds such as sodium tanshinone IIA [34] and resveratrol [29] exhibit beneficial effects on injured heart. Previous studies suggested that Gen protects against myocardial ischemia/reperfusion injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone VI protects the myocardium against I/R injury and attenuates the progression of myocardial remodeling in vitro [119]. Tan IIA attenuates the expression of angiotensin II-induced collagen type I, ROS formation, and the proliferation of cardiac fibroblasts [120, 121]. Recent research also demonstrates that Tan IIA inhibits extracellular matrix remodeling induced by angiotensin II in human cardiac fibroblasts through inhibition of Smad signaling and MMP-9 expression via nuclear localization of NF- κ B [122].…”
Section: Resultsmentioning
confidence: 99%
“…Tan IIA can inhibit these reactions, which have been mentioned in the above experiments [8, 28–32]. To test the hypothesis that Tan IIA can alter the expression and/or activity of specific antioxidant enzymes to prevent cells from oxidant damage, at least three experiments [38, 43, 44] were conducted and demonstrated that the cell protective effect of Tan IIA was mediated primarily by induction of glutathione peroxidase (GPx) gene expression and activity, as well as other antioxidant enzyme activities in the heart.…”
Section: Cardiovascular Pharmacologymentioning
confidence: 99%